2007
DOI: 10.1002/nbm.1143
|View full text |Cite
|
Sign up to set email alerts
|

Elevating tensor rank increases anisotropy in brain areas associated with intra‐voxel orientational heterogeneity (IVOH): a generalised DTI (GDTI) study

Abstract: Rank-2 tensors are unable to represent multi-modal diffusion associated with intra-voxel orientational heterogeneity (IVOH), which occurs where axons are incoherently oriented, such as where bundles intersect or diverge. Under this condition, they are oblate or spheroidally shaped, resulting in artefactually low anisotropy, potentially masking reduced axonal density, myelinisation and integrity. Higher rank tensors can represent multi-modal diffusion, and suitable metrics such as generalised anisotropy (GA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 28 publications
2
21
2
Order By: Relevance
“…For l ¼ 2, GA is akin to FA. GA and SE are not rankinvariant, and it has been shown both in simulations and on the basis of data acquired in vivo that they increase with rank in regions where IVOH is present (50,74). Their relative merits remain to be characterized: while from a theoretical viewpoint SE may be preferable since it is not clear why the square of the difference and not any other power should be considered in the definition of GA, from a computational viewpoint GA is preferable since the logarithm in the entropy function forces to resort to numerical integration (74).…”
Section: Generalised Diffusion Tensor Imagingmentioning
confidence: 97%
See 3 more Smart Citations
“…For l ¼ 2, GA is akin to FA. GA and SE are not rankinvariant, and it has been shown both in simulations and on the basis of data acquired in vivo that they increase with rank in regions where IVOH is present (50,74). Their relative merits remain to be characterized: while from a theoretical viewpoint SE may be preferable since it is not clear why the square of the difference and not any other power should be considered in the definition of GA, from a computational viewpoint GA is preferable since the logarithm in the entropy function forces to resort to numerical integration (74).…”
Section: Generalised Diffusion Tensor Imagingmentioning
confidence: 97%
“…Since rank-2 tensors can represent only a single directional diffusivity maximum, least-squares fitting results in oblate-shaped ellipsoids when more than one directional orientation is present: in such a case, the direction of the principal eigenvector e 1 conveys no useful information, and anisotropy indexes from rank-2 tensors are no longer valid indicators of axonal density (50,(53)(54)(55).…”
Section: ¼1: ½78mentioning
confidence: 98%
See 2 more Smart Citations
“…As a consequence, the apparent diffusion coefficient (ADC) that one measures depends on the b-value [1][2][3]. It has also been shown that, at the millimetre-scale resolution which is typical of current in vivo imaging studies, intersecting axonal bundles and partial volume effects introduce intra-voxel orientational heterogeneity; as a consequence, rank-2 tensors may take an oblate 123 shape, biasing measurements of anisotropy to artificially low values which are often interpreted as indicating low axonal density [4][5][6].…”
Section: Introductionmentioning
confidence: 98%